High-altitude adaptation as a protective factor against postoperative pulmonary complications in liver resection: a prospective matched cohort study - Qingyong Luo; Yu Zhang; Shiyao Gu; Li liu; Si Zeng; Qian Lei (BMC Anesthesiology)
Abstract Background High-altitude adaptation (HAA), induced by chronic hypoxia, has clinically significant cardioprotective effects; however, its impact on postoperative pulmonary complications (PPCs) in patients undergoing liver resection remains uncertain. Methods We conducted a single-center prospective matched cohort study enrolling 292 consecutive patients undergoing elective liver resection. Patients were divided into two groups based on their long-term residential altitude: high-altitude group (≥ 1500 m) and plain group (< 1500 m). Propensity score matching (1:2 ratio) was applied to control for confounding factors, including demographic variables, clinical characteristics, preoperative oxygen saturation, ARISCAT score, and surgical factors. The primary outcome was the incidence of PPCs within 7 days after surgery. Secondary outcomes included the severity of PPCs, surgical complication grading, and length of hospital stay. Statistical analysis was performed using R software and SPSS 22.0. Results After matching, 212 patients were included in the analysis. The incidence of PPCs within 7 days postoperatively in the high-altitude group was significantly lower than that in the plain group (61.5% vs. 76.1%, RR 0.80, 95% CI 0.66–0.98, P = 0.024). Furthermore, the high-altitude group showed milder complication severity and a shorter hospital stay (6 [4–8] vs. 7 [5–11] days, P = 0.005). Multivariate logistic regression analysis showed that HAA was an independent protective factor against PPCs (OR 0.31, 95% CI 0.12–0.83, P = 0.020). Further exploratory analysis revealed that during hepatic pedicle clamping, blood glucose levels remained more stable in the high-altitude group ([9.30 [7.25–11.90] vs. 10.95 [7.90–14.00] mmol/L, P < 0.001), with lower lactate accumulation after multiple clamps (1.55 [1.10–2.17] vs. 1.70 [1.10–2.50] mmol/L, P = 0.042). Conclusion HAA may reduce the incidence and severity of PPCs after liver resection, potentially due to enhanced metabolic stability associated with chronic hypoxia in high-altitude residents. Trial registration This study is registered with ChiCTR (ID: ChiCTR2200061915), registered on July 11, 2022.